2016
DOI: 10.1155/2016/3296307
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Surface Toll-Like Receptor 9 Expression with IL-17 Production in Neutrophils during Septic Peritonitis in Mice Induced byE. coli

Abstract: IL-17 is a proinflammatory cytokine produced by various immune cells. Polymorphonuclear neutrophils (PMNs) are the first line of defense in bacterial infection and express surface Toll-like receptor 9 (sTLR9). To study the relationship of sTLR9 and IL-17 in PMNs during bacterial infection, we infected mice with E. coli intraperitoneally to establish a septic peritonitis model for studying the PMNs response in peritoneal cavity. We found that PMNs and some of “giant cells” were massively accumulated in the peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
12
0
2
Order By: Relevance
“…In recent years, neutrophils have been found to express sTLR9 which is potentially able to engage DAMPs, such as mtDNA released from necrotic cells during sterile inflammation. Till date, only a few studies exist describing the function of neutrophil sTLR9 27 , 35 and they largely propose an involvement in detrimental effects by provoking massive proinflammatory cytokine production. Thus, sTLR9-expressing neutrophils are key players in inducing rapid inflammation 36 , promoting sepsis or SIRS 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, neutrophils have been found to express sTLR9 which is potentially able to engage DAMPs, such as mtDNA released from necrotic cells during sterile inflammation. Till date, only a few studies exist describing the function of neutrophil sTLR9 27 , 35 and they largely propose an involvement in detrimental effects by provoking massive proinflammatory cytokine production. Thus, sTLR9-expressing neutrophils are key players in inducing rapid inflammation 36 , promoting sepsis or SIRS 37 .…”
Section: Discussionmentioning
confidence: 99%
“…In peritoneal biopsies of PD patients, a double positive staining for IL-17A and neutrophil markers (such as myeloperoxidase) was found, suggesting that neutrophils may produce IL-17A [ 35 ]. In septic peritonitis induced by E. coli infection, one study showed that higher numbers of polymorphonuclear neutrophils accumulated in the peritoneal cavity of mice with a septic peritonitis episode and increased their IL-17 expression during infection [ 65 ]. However, recent data suggest that cultured human neutrophils do not express IL-17A, but that it may instead be released from neutrophil extracellular traps (NETs) [ 33 , 66 ].…”
Section: Il-17a: a Key Proinflammatory Cytokine And Therapeutic Tamentioning
confidence: 99%
“…In a mouse model of lipopolysaccharide (LPS)-induced peritonitis, a macrophage polarization was linked to the development and progression of infection through JAK/STAT signaling pathway [ 197 ]. Mice with E. coli peritonitis showed an increased IL-17A expression in immune cells including CD11b + and CD11b − neutrophils, macrophages, and CD3 + T cells [ 65 ]. In patients with cirrhosis and peritonitis, serum levels of the M2 macrophage marker CD206 were increased and associated with mortality risk [ 198 ].…”
Section: Peritoneal Impact Of Il-17amentioning
confidence: 99%
“…The clinical manifestations of the mice were assessed with a clinical score (CS), which is defined based on the signs of lethargy, piloerection, tremor, periorbital exudates, respiratory distress, and diarrhoea. 48 The mice with a CS > 3 or ≤3…”
Section: Adjuvanticity Of Tios For Microbial Vaccines In Micementioning
confidence: 99%